Paseamos para reconocer cuadriláteros - Lopez Alvarado, Eligio (2018)
Mathematics is a human activity and occupies a relevant place in the development of knowledge and culture in our societies. It is in constant development and readjustment, and therefore supports a growing variety of research in science, modern technologies and others, which are fundamental for the integral development of the country. This learning area contributes to the formation of citizens capable of searching, organizing, systematizing and analyzing information, understanding the world around them, developing in it, making relevant decisions and solving problems in different contexts in a creative way.